Health for all by the year 2000 and primary health care: the Turkish case - Tatar, Mehtap (1992)
This study aims at analyzing Turkish health policy from a Primary Health Care perspective as pronounced in Alma-Ata, 1978. The Alma-Ata Declaration has long been regarded as a watershed in the health field and 134 countries, including Turkey, have endorsed the Declaration showing their support for the views expressed in the Document. However, although the international community gave its full support, in practice, different interpretations and implementation of the principles have emerged.